Navigating Road Safety: Factors, Legislations, Safety Audits, Technological Advances and Challenges in Nepal - Hada, Sakar; Khadka, Raship (KTFT Journal, 2024)
Road transportation has become increasingly lethal, highlighting a need for swift implementation and road safety measures and enhanced study to develop more effective safety strategies. All factors related to the road environment, including road design, human behaviour, and vehicle characteristics, should be thoroughly inspected to more accurately and precisely understand their involvement in road accidents. Currently, the state of road-related legislation, databases, and technologies in Nepal is poor compared to other countries. The road safety bill has been pending since 2017, leaving the National Road Safety Council (NRSC) without clear ownership and resources. Developing countries like Nepal tend to prioritize infrastructure development over the management of resources for road safety audits. Prioritizing the introduction of effective road safety policies is critical, as further delays will result in preventable loss of human life and significant monetary costs. Nepal’s challenging terrain and low-income status make it difficult to design, construct, operate and maintain roads to the highest standards. However, with the availability of more affordable hardware and advanced software, there should be a clear focus on utilizing these tools to improve road safety and address these challenges. The development of the Kathmandu-Terai Fast Track brings with it a significant responsibility to maintain road safety.